Pengaruh Irisin pada Pencoklatan Lemak Putih - Natalia Danayati (Jurnal Ilmiah Kesehatan Sandi Husada, 2021)
Introduction: Irisin is a new myokine that links physical activity to increased metabolic performance and is associated with the browning of white adipose tissue to brown. Objective: To determine the effect of irisin on the browning of white fat. Methods: Using literature studies from scientific sources by summarizing publications and comparing the results presented. Results: Irisin, which is secreted from muscle, stimulates the expression of uncoupling protein 1 (UCP1) in adipocytes that causes browning of white adipose tissue via p38 mitogen-activated protein kinase (MAPK) and via extracellular-signal-regulated kinase (ERK). Conclusion: Irisin secreted by skeletal muscle will express UPC-1 in adipose tissue which causes white adipose tissue to brown and increase thermogenesis activity.